Seven new species of Lasioglossum (Dialictus) Robertson, 1902 (Hymenoptera: Halictidae: Halictini) from the Yucatán Peninsula, Mexico - Landaverde-González, Patricia; Gardner, Joel; Moo-Valle, Humberto; Quezada-Euán, José Javier G.; Ayala, Ricardo; Husemann, Martin (European Journal of Taxonomy, 2023)
Lasioglossum is a large genus of halictid bees with high species diversity in morphologically rather cryptic species groups. With more than 1900 described species, the taxonomy of the genus is complex and largely unresolved in many regions. For practical reasons, systematic reviews are restricted in scope either geographically or to particular species groups. In this study we focus on the subgenus Dialictus of the genus Lasioglossum from the Yucatán Peninsula in Mexico. In previous studies we identified members of the genus as important pollinators of cash crops in the region, and genetic analyses suggested the existence of seven molecular taxonomic units (mOTU). Based on additional morphological differences, we here describe these mOTUs as novel species, Lasioglossum (Dialictus) yucatanense Landaverde-González sp. nov., L. (D.) paxtoni Landaverde-González sp. nov., L. (D.) ameshoferi Landaverde-González sp. nov., L. (D.) aureoviride Landaverde-González & Husemann sp. nov., L. (D.) paralepidii Gardner sp. nov., L. (D.) milpa Landaverde-González sp. nov. and L. (D.) nanotegula Landaverde-González & Husemann sp. nov., and provide keys and images to assist in their identification.